Anthropometric and physiological profiles in Spanish downhill skiing competitors - Gomez-Lopez, P. J.; Ruperez, O. H.; de Almiron-Medias, P. R. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: The need to optimize the individual performance of Spanish skiers and detect new talents to improve the performance of the national team members motivated us to conduct this study.